Sustainable desalination: Long-term monitoring of brine discharge in the marine environment. (December 2020) - Sola, Iván; Fernández-Torquemada, Yolanda; Forcada, Aitor; Valle, Carlos; del Pilar-Ruso, Yoana; González-Correa, José M.; Sánchez-Lizaso, José Luis
Abstract: The environmental impact of desalination is the most important concern related to its sustainable development. We present the results of a long-term environmental plan to monitor brine discharge (BD) from a desalination plant located in a high environmental value area in Spain. Generalized additive models were used to analyze the biological parameters of biological communities. Results of 17 years of BD monitoring show how its environmental impact can be minimized through well-planned decision-making between scientists and industry. The brine dilution prior to its discharge into an artificial channel of low ecological value significantly reduced the brine influence area. P. oceanica shoot production and echinoderms abundances were relatively stable across historical series and similar values in control and impacts locations were observed. Conversely, there was a higher abundance and species richness of fishes in the BD area. The important findings reported here should be considered for future applications in similar projects. Highlights: A 17-year-long effluent monitoring in high-value area is presented. Seawater bypassing effective to dilute the brine discharge Long-term monitoring demonstrates no impact on marine ecosystems. Higher abundance and diversity of fish were observed in brine discharge area. Cooperation between environmental scientist and industry for sustainable SWRO